The Effect of Trans-Abdominal Chorionic Villus Sampling on Fetal Heart Rate and Placental Vascular Resistance Index: A Color Doppler Ultrasound Study - Nazanin Farshchian (Acta Medica Iranica, 2021)
Fetal hemodynamic changes can occur immediately following invasive chorionic villus sampling (CVS). We decided to study the possible effect of CVS on fetal heart rate (FHR), and uteroplacental resistance index (RI) changes using color Doppler ultrasound. Thirty-five pregnant patients with a gestational age of more than 12 weeks were included. Trans-abdominal CVS was done to assess the possibility of thalassemia. Before and after the CVS, color Doppler ultrasound was done to measure FHR and uteroplacental RI. Mean (SD) values for FHR before and after the CVS were 175.22 (±9) and 173.62 (±9.94) beats per minute, respectively; P=0.18. Mean (SD) uteroplacental RI before the CVS was 0.79 (0.07) which significantly increased to 0.82 (0.08); P=0.03. We observed a significant increase in resistance of blood flow in placental circulation after CVS. However, no significant change was observed regarding FHR after CVS.